PENERAPAN E-GOVERNMENT MENDORONG TERWUJUDNYA PENYELENGGARAAN PEMERINTAHAN YANG BAIK DI INDONESIA (Tanggapan terhadap Instruksi Presiden Republik Indonesia Nomor 3 Tahun 2003) - Veronica Kumurur,dkk (PPLH-SDA, Lembaga Penelitian Unsrat Manado, 2013)
Based on observations carried out in order to arrange Appendix I of Presidential Instruction No. 3 of 2003 stated that there are still some weaknesses that stand out for the formation of E-Government is the human resource constraints that hinder effective work processes, the rigid bureaucratic system, the absence of adequate strategies and that the lack of funds, there is still no coordination among the sectors to joint together to build a network of communication and information, and is still a limited capacity for communities to access these networks via the Internet. In addition, standardization of procedures and operational implementation of E-Government is a must for the government to set one up. From several weaknesses mentioned above, can be summed up that there are three things that mattered to implement E-Government to support the creation of Good Governance, namely: (1) Readiness of human resources; (2) bureaucracy or the State Organization, (3) Limitations of budget resources or funds; and (4) standardization of implementation and the basis for regulation. Of the problems mentioned above, the ability and readiness of governments to implement E-Government both in terms of human resources, the readiness of the bureaucracy, technological readiness and preparedness of communities as users need to be studied in depth. It is solely to determine the readiness and the benefits that would be obtained if the application of E-Government is set. Therefore, the purpose of writing this paper are: (a) to assess the extent of readiness of existing human resources to deal with the implementation of E-Government; and (b) to examine the extent to which the implementation of E-Government can influence the creation of Good-Governance seen from bureaucracy and the state administration has been running until today